2008
DOI: 10.1038/jcbfm.2008.112
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Assessment of Regional Cerebral Blood Flow after Asphyxial Cardiac Arrest in Immature Rats

Abstract: Cerebral blood flow (CBF) alterations after asphyxial cardiac arrest (CA) are not defined in developmental animal models or humans. We characterized regional and temporal changes in CBF from 5 to 150 mins after asphyxial CA of increasing duration (8.5, 9, 12 min) in postnatal day (PND) 17 rats using the noninvasive method of arterial spin-labeled magnetic resonance imaging (ASL-MRI). We also assessed blood-brain barrier (BBB) permeability, and evaluated the relationship between CBF and mean arterial pressure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
77
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(86 citation statements)
references
References 40 publications
9
77
0
Order By: Relevance
“…1,4 We previously showed that pretreatment of dV1-1 before ACA can enhance perfusion 24 hours after ischemia, resulting in improved neuronal survival in the hippocampal CA1 and cortex regions in our rat model of ACA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,4 We previously showed that pretreatment of dV1-1 before ACA can enhance perfusion 24 hours after ischemia, resulting in improved neuronal survival in the hippocampal CA1 and cortex regions in our rat model of ACA.…”
Section: Introductionmentioning
confidence: 99%
“…3 Inhibition of PKCd (via specific inhibitor of PKCd, dV1-1) can cause a revival of CBF 24 hours after ischemia to counteract hypoperfusion or low CBF found to be suppressed after cardiac arrest from 38% to 65%. 1,4 We previously showed that pretreatment of dV1-1 before ACA can enhance perfusion 24 hours after ischemia, resulting in improved neuronal survival in the hippocampal CA1 and cortex regions in our rat model of ACA. 1 Here, we sought out to define the specific mechanism(s) of how inhibition of PKCd can alleviate these pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…CPR research depends mostly on the use of animal models that are designed to simulate CA in humans. 19 -21 The animal models that have been used in studies are swine, rodents, 22,23 canines, 24,25 primates, 26 rabbits, sheep 27 and cats. 28 Among others, asphyxial arrest in animals such as rhesus monkeys, rabbits and sheep were extensively studied in the 1960s by Dawes and colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…Several therapies have shown promise in this model, e.g., mild hypothermia, glucose and insulin, and neurotensin [223,[226][227][228][229]. There also are pediatric analogs [230][231][232][233], which use post-natal Day 17 rats. Promising results have been obtained with hypothermia and minocycline [231,233].…”
Section: Rat Aca Modelsmentioning
confidence: 99%